Risk of drug interaction: combination of antidepressants and other drugs Risco de interação de drogas: combinações de uso de antidepressivos e outras drogas - Lincoln Sakiara Miyasaka; Alvaro Nagib Atallah (Universidade de São Paulo, 2003)
OBJECTIVE: To assess the frequency of combination of antidepressants with other drugs and risk of drug interactions in the setting public hospital units in Brazil. METHODS: Prescriptions of all patients admitted to a public hospital from November 1996 to February 1997 were surveyed from the hospital's data processing center in São Paulo, Brazil. A manual search of case notes of all patients admitted to the psychiatric unit from January 1993 to December 1995 and all patients registered in the affective disorders outpatient clinic in December 1996 was carried out. Patients taking any antidepressant were identified and concomitant use of drugs was checked. By means of a software program (Micromedex®) drug interactions were identified. RESULTS: Out of 6,844 patients admitted to the hospital, 63 (0.9%) used antidepressants and 16 (25.3%) were at risk of drug interaction. Out of 311 patients in the psychiatric unit, 63 (20.2%) used antidepressants and 13 of them (20.6%) were at risk. Out of 87 patients in the affective disorders outpatient clinic, 43 (49.4%) took antidepressants and 7 (16.2%) were at risk. In general, the use of antidepressants was recorded in 169 patients and 36 (21.3%) were at risk of drug interactions. Twenty different forms of combinations at risk of drug interactions were identified: four were classified as mild, 15 moderate and one severe interaction. CONCLUSION: In the hospital general units the number of drug interactions per patient was higher than in the psychiatric unit; and prescription for depression was lower than expected. OBJETIVO: Verificar a freqüência de combinações de antidepressivos com outros medicamentos e o risco de interações medicamentosas em um hospital público no Brasil. MÉTODOS: Prescrições de todos os pacientes internados em um hospital público, em São Paulo, SP, de novembro de 1996 a fevereiro de 1997 foram analisadas pelo centro de processamento de dados do hospital. Foi realizada busca manual de todos os prontuários de pacientes internados na enfermaria de psiquiatria do hospital de janeiro de 1993 a dezembro de 1995, assim como de todos os pacientes registrados no ambulatório de doenças afetivas em dezembro de 1996. Foram identificados os pacientes que usaram algum antidepressivo e as drogas utilizadas concomitantemente. Foram identificadas pelo programa Micromedex® as interações medicamentosas. RESULTADOS: Dentre os 6.844 pacientes internados nas enfermarias gerais (não psiquiátricas) do hospital, 63 usaram antidepressivos (0,9%) e 16 (25,3%) usavam medicações com risco de interação. Dentre os 311 pacientes da enfermaria de psiquiatria, 63 (20,2%) usavam antidepressivos e 13 (20,6%) apresentavam risco de interação. Dos 87 pacientes do ambulatório de doenças afetivas, 43 (49,4%) usavam antidepressivos e 7 (16,2%) apresentavam risco. Em geral, o uso de antidepressivos foi encontrado em 169 pacientes e 36 (21,3%) estavam em risco de interação medicamentosa. Vinte diferentes tipos de interações foram identificados, sendo 4 leves, 15 moderados e um grave. CONCLUSÕES: Nas enfermarias gerais o número de interações medicamentosas foi superior em relação à enfermaria de psiquiatria; e o número de prescrições de antidepressivos foi menor do que o esperado.